Analysis of Thermodynamic Properties for Rare Earth Complexes in Ionic Liquids by Raman Spectroscopy and DFT Calculation - Matsumiya, Masahiko; Kazama, Ryo; Tsunashima, Katsuhiko (Journal of Applied Solution Chemistry and Modeling, 2016)
The coordination states of the divalent and trivalent rare earth complexes in ionic liquid, triethyl-pentyl-phosphonium bis(trifluoromethyl-sulfonyl) amide [P2225][TFSA] were investigated by Raman spectroscopy and DFT calculation. The concentration dependences of the deconvoluted Raman spectra were investigated for 0.23-0.45 mol kg-1 RE(III), RE=Nd and Dy, and the mixed sample of RE(II)/RE(III)=1/3 at the molar ratio in [P2225][TFSA]. According to the conventional analysis, the solvation number; n of rare earth complexes in [P2225][TFSA] were determined to be n=4.06 for Nd(II), 5.01 for Nd(III), 4.12 for Dy(II) and 5.00 for Dy(III). Thermodynamic properties such as ΔisoG, ΔisoH and ΔisoS for the isomerism of [TFSA]- from trans- to cis-isomer in bulk and the first solvation sphere of the centered [RE3+] cation in [P2225][TFSA] were evaluated from the temperature dependence in the range of 298-398K. ΔisoG(bulk), ΔisoH(bulk) and TΔisoS(bulk) at 298 K were -1.06, 6.86, and 7.92 kJ mol-1, respectively. The trans-[TFSA]-was dominant in the enthalpy due to the positive value of ΔisoH(bulk) and TÎ”isoS(bulk) was slightly larger than ΔisoH(bulk), so that cis-[TFSA]- was revealed to be an entropy-controlled in [P2225][TFSA]. On the other hand, in the first solvation sphere of [RE3+] cation, ΔisoH (Nd)(-47.39 kJ mol-1) increased to the negative value remarkably and implied that the cis-[TFSA]- isomers were stabilized for enthalpy. ΔisoH(Nd) contributed to the remarkable decrease in the ΔisoG(Nd) and this result clearly indicated that the cis-[TFSA]- bound to Nd3+ cation was preferred and the coordination state of [Dy(III)(cis-TFSA)5]2- was stable in [P2225][TFSA] The optimized geometries and the bonding energies of [RE(II)(cis-TFSA)4]2- and [RE(III)(cis-TFSA)5]2- clusters were also investigated from DFT calculation with ADF package. The bonding energy; ΔEb was calculated from ΔEb= Etot(cluster) - Etot(RE2,3+) - nEtot([TFSA]-). ΔEb([Nd(II)(cis-TFSA)4]2-), ΔEb([Nd(III)(cis-TFSA)5]2-), ΔEb([Dy(II)(cis-TFSA)4]2-) and Î”Eb([Dy(III)(cis-TFSA)5]2-) were -2241.6, -4362.3, -2135.4 and -4284.2 kJmol-1, respectively. This result was revealed that [RE(III)(cis-TFSA)5]2-cluster formed stronger coordination bonds than [Dy(II)(cis-TFSA)4]2- cluster. The average atomic charges and the bond distances of these clusters were consistent with the thermodynamic properties.